Quality Analysis of Scheduling System Using COBIT 2019 at Ministry of Religious Affairs Pasuruan - Aulia, Latifa Riska; Amrozi, Yusuf; Milad, M. Khusnu; Permadi, Andhy (Universitas Multimedia Nusantara, 2024)
This study aims to measure the quality scheduling information system (SIP KEMENAG) of Ministry of Religious Affairs (MORA) in Pasuruan Regency. In this study, the author used a combination or mixed methods research with a sequential explanatory model. The combination research method with a sequential explanatory model is characterized by the collection and analysis of quantitative data in the initial stage, followed by qualitative data explanation in the next stage. The website quality analysis process using COBIT 2019 produced an average maturity score: BAI3 (4.14), BAI4 (4.34), and DSS5 (4.32). After averaging, the SIP KEMENAG application is at level 4 (quantitatively managed) in the capability maturity model integration. This shows that the application has adopted an approach based on data and numbers to plan, measure, and control the performance of the application process. The desired value is level 5 (optimizing), with a gap of 0.73. After the quantitative data is found, in-depth information mining or interviews will be carried out using qualitative methods.